1999
DOI: 10.1007/s001980050236
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Postmenopausal Women with Osteoporosis or Low Bone Density with Raloxifene

Abstract: Raloxifene, a selective estrogen receptor modulator (SERM), has been shown to improved bone mineral density (BMD) and serum lipid profiles in healthy postmenopausal women. The objective of this study was to examine the effects of raloxifene on BMD, biochemical markers of bone metabolism and serum lipids in postmenopausal women with low bone density or osteoporosis. This Phase II, multicenter, 24-month, double-masked study assessed the efficacy and safety of raloxifene in 129 postmenopausal women (mean age +/- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(37 citation statements)
references
References 26 publications
3
32
1
1
Order By: Relevance
“…However, unexpectedly, the increase rate of BMD of LS was somewhat higher than that observed in the previous studies [1][2][3][4][5][6]. This apparent difference may be partly due to the variability in BMD values resulting from the small sample size in our study, or because about one third of our patients were treated with combined use of RLX and ALF, suggesting that RLX in combination with ALF may be potentially more beneficial for bone health than RLX alone.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…However, unexpectedly, the increase rate of BMD of LS was somewhat higher than that observed in the previous studies [1][2][3][4][5][6]. This apparent difference may be partly due to the variability in BMD values resulting from the small sample size in our study, or because about one third of our patients were treated with combined use of RLX and ALF, suggesting that RLX in combination with ALF may be potentially more beneficial for bone health than RLX alone.…”
Section: Discussioncontrasting
confidence: 71%
“…A number of clinical trials [1][2][3][4][5][6] evaluating the effects of RLX on bone, including MORE trial [1], the largest double-blind placebo-controlled one, have clearly demonstrated that RLX improves accelerated bone turnover, increases bone mineral density (BMD) at the lumbar spine (LS) and at the femoral neck (FN), and reduces the risk of new vertebral fractures. In addition, favorable effects on lipid metabolism have also been repeatedly reported in the literature [2,3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Estrogen has a major role in regulation of the bone formation-resorption equilibrium, as it stimulates osteoblast activity 48 . Some SERMs such as raloxifene, act on the bone by slowing bone resorption by the osteoclasts.…”
Section: Raloxifenementioning
confidence: 99%
“…Ten million individuals are affected with osteoporosis, and an additional 18 million with low bone mass are at risk. (1) Osteoporosis is more prevalent in postmenopausal white women, (1,2) and it is a preventable disease of menopause. (3) Bone resorption and formation is at equilibrium before menopause, and after menopause, resorption increases, resulting in bone loss.…”
Section: Introductionmentioning
confidence: 99%